A MARXIST APPROACH IN READING PERCY BYSSHE SHELLEYâ€™S â€œSONG TO THE MAN OF ENGLANDâ€ (Universitas Pamulang, 2019)
This study is aimed to uncover some Marxist issues in one famous poetry in Romantic period: Percy Bysshe Shelley's